Visual Comfort in Modern University Classrooms - Yun-Shang Chiou (Sustainability, 2020)
Universities are at the front line of promoting sustainability. The wellbeing of its students plays a key role in advancing such agendas. In the past decade, many university classrooms have been equipped with a projector; however, the lighting design of the classroom remains unchanged. This paper presents a visual comfort study of modern university classrooms by considering three working surfaces: the student’s desk, whiteboard, and projector screen. The study cross-examines the quality of the classroom lighting by high dynamic range image (HDRi) photography and the students’ well-being from user satisfaction surveys. Comparisons are organized based on the seating area of the student, the type of learning (text-based or image-based) in the classroom, and the lighting scene with and without a projector in use. The spot illuminance, luminance, HDRi spatial luminance distribution and the Unified Glare Rating (UGR) are the parameters used to describe lighting quality. This paper found that more than 70% of the respondents experienced some adverse physical symptoms, and nearly 50% felt that the lighting condition was not ideal for task performance. UGR indicated the presence of minor glare problems in whiteboard-based teaching scenarios, and daylight was too strong to be utilized. The results suggest that the lighting design needs to involve a luminance distribution minded approach for the students’ wellbeing in classroom learning.